1979
DOI: 10.3109/inf.1979.11.issue-2.04
|View full text |Cite
|
Sign up to set email alerts
|

Hearing Impairment in Meningococcal Meningitis*

Abstract: Hearing affection as a sequel of meningococcal meningitis and its relation to age, sex, severity and duration of disease was studied in Cairo, Egypt during the period December 1966--December 1973. The total incidence of impaired hearing in the 775 cases was 5.8%. This incidence was higher in the younger age groups, females, severe cases of meningitis and in patients who received specific therapy shortly after the onset of signs and symptoms of the disease. The aetiology of hearing impairment in meningitis was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
2
0
3

Year Published

1984
1984
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
1
2
0
3
Order By: Relevance
“…This rate falls at the lower end of other reported outcomes for meningococcal meningitis. 5,17,18 It was similar to the 3.2% rate reported from a 24‐year retrospective study of meningococcal disease. 19 This study also identified a variation in the rate of sensorineural impairment depending on the meningococcal serogroup.…”
Section: Discussionsupporting
confidence: 81%
“…This rate falls at the lower end of other reported outcomes for meningococcal meningitis. 5,17,18 It was similar to the 3.2% rate reported from a 24‐year retrospective study of meningococcal disease. 19 This study also identified a variation in the rate of sensorineural impairment depending on the meningococcal serogroup.…”
Section: Discussionsupporting
confidence: 81%
“…Puede progresar rápidamente y ocasionar el deceso o secuelas. De ellas, la más importante es la sordera que acontece hasta en 10% (1) de los casos y en casos cuya etiología es el (2) meningococo puede ser de 5,8% .…”
Section: Introductionunclassified
“…Existen pocos reportes de la asociación de ataxia y sordera aguda en pacientes con meningitis por (11)(12)(13)(14) meningococo .…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Several studies have reported an increased incidence of bacterial meningitis in children (Granoff and Daum 1980, Schlech et al 1985, Salwen et al 1987. Although the mortality rate has decreased in recent years, bacterial meningitis is still frequently associated with a number of long-term neurological sequelae and permanent hearing impairment (Rosenhall et al 1978, Habib et al 1979, Richner et al 1979, Berlow et al 1980, Ozdamar el al. 1983, Vienny et al 1984, Salwen et al 1987.…”
mentioning
confidence: 99%